ANALISIS STRATEGI PENGELOLAAN PRODUKSI USAHA TERNAK AYAM PETELUR BERDASARKAN PERSPEKTIF MANAJEMEN SYARIAH (STUDI KASUS DI NAGARI SIMPANG KAPUAK KECAMATAN MUNGKA KABUPATEN LIMA PULUH KOTA) - Suci Maha Rani; Novera Martilova (Jurnal Ekonomi dan Bisnis, 2023)
Livestock is an activity intended for the maintenance and breeding of livestock whose purpose is to obtain results and benefits from these activities. Livestock is an agricultural sub-sector that includes management of livestock production facilities, livestock management, and marketing. Therefore a strategy is needed in running the company so that the company can exist in the long term. Strategy is a set of integrated actions that become a tool to increase long-term success and strength to achieve competitive advantage. This research was conducted through qualitative research. Data analysis techniques are used to reduce, present, draw conclusions and verify data. Research in this field shows that the strategy for managing cocoon production is a strategy for making good coops to protect chickens from climate and weather changes. Seed selection strategy, selected seeds to produce quality eggs. Chicken care and health strategies through administration of vaccines and vitamins so that the growth of chickens is age-appropriate and healthy, as well as strategies for choosing feed to meet the nutritional needs and nutritional needs of chickens.